Effects of conversion from boreal natural wetlands to rice paddy fields on the dynamics of total dissolved iron during extreme precipitation events. (March 2020) - Guan, Jiunian; Qi, Kun; Wang, Junyang; Zhuang, Jiahui; Yuan, Xing; Yan, Baixing; Lu, Nan; Qu, Jiao
Abstract: Natural wetlands play a critical role in increasing the total dissolved Fe (TDFe) concentration in boreal fluvial systems. In the Sanjiang Plain, which is the largest concentrated distribution area of natural wetlands in China, over 80% of the natural wetlands have been converted to rice paddy fields (RPFs) during the last six decades; the altered hydrological processes are hypothesized to influence the dynamics of TDFe, particularly during extreme precipitation events (EPEs). In the current study, the TDFe dynamics in typical natural freshwater wetlands in the Sanjiang Plain were elucidated. The TDFe species including Fe(II), Fe(III) and colloidal Fe, were monitored in a Deyeucia angustifolia wetland (DAW), Carex lasiocarpa wetland (CLW), and RPF during the rainy season from 2012 to 2014. Compared to normal precipitation days, the average TDFe concentration increased significantlys in all wetlands during the EPEs, among which the fluctuation of TDFe during the EPEs was more largely in the RPF than in the natural wetlands. The dynamics of the TDFe speciation in the different wetlands also showed different patterns; moreover, TDFe and its species showed a significantly positive relationship with dissolved organic matter. With an increasing frequency of EPEs anticipated by climate change models, our results suggest higher levels of TDFe will be transported to the Amur River and Okhotsk Sea, which may potentially affect TDFe cycling, water quality and ecosystem dynamics. Graphical abstract: Image 1 Highlights: With frequent EPEs, natural wetland conversion significantly increased TDFe flux. Higher TDFe export during EPEs were observed in RPF compared to unconverted wetlands. TDFe speciation varied in different patterns during EPEs in different wetland types. TDFe concentrations were positively correlated to DOC and HIX in all the wetlands. Natural wetland conversion potentially influences aquatic ecosystems via TDFe cycle.